Analytical current THD evaluation for three‐phase voltage source inverters. Issue 6 (1st May 2020) - Akhmetov, Zhansen; Ruderman, Alex
Abstract : This study addresses the calculation of current total harmonic distortion (THD) for three‐phase (3P) pulse‐width modulation (PWM) inverters. First, it demonstrates how an analytical approach to PWM current ripple normalised mean square (NMS) calculation introduced in the late 1980s for a two‐level (2L) inverter can be used for current THD evaluation. Second, it is shown how to evaluate current THD for a three‐level (3L) 3P inverter using the current ripple NMS concept. Though considered is a 3P cascaded inverter with one H‐bridge per phase, the results are applicable to popular 3L neutral point clamped (T‐type) and flying capacitor inverters.